Optic, trigeminal, and facial neuropathy related to anti‐neurofascin 155 antibody - Ogata, Hidenori (Ann Clin Transl Neurol, 2020)
OBJECTIVE: To characterize the frequency and patterns of optic, trigeminal, and facial nerve involvement by neuroimaging and electrophysiology in IgG4 anti‐neurofascin 155 antibody‐positive (NF155(+)) chronic inflammatory demyelinating polyneuropathy (CIDP). METHODS: Thirteen IgG4 NF155(+) CIDP patients with mean onset age of 34 years (11 men) were subjected to neurological examination, blink reflex, and visual‐evoked potential (VEP) testing, and axial and/or coronal T2‐weighted head magnetic resonance imaging (MRI). RESULTS: Among 13 patients, facial sensory impairment, facial weakness, and apparent visual impairment were observed in three (23.1%), two (15.4%), and two (15.4%) patients, respectively. All 12 patients tested had blink reflex abnormalities: absent and/or delayed R1 in 11 (91.7%), and absent and/or delayed R2 in 10 (83.3%). R1 latencies had strong positive correlations with serum anti‐NF155 antibody levels (r = 0.9, P ≤ 0.0001 on both sides) and distal and F wave latencies of the median and ulnar nerves. Absent and/or prolonged VEPs were observed in 10/13 (76.9%) patients and 17/26 (65.4%) eyes. On MRI, hypertrophy, and high signal intensity of trigeminal nerves were detected in 9/13 (69.2%) and 10/13 (76.9%) patients, respectively, whereas optic nerves were normal in all patients. The intra‐orbital trigeminal nerve width on coronal sections showed a significant positive correlation with disease duration. INTERPRETATION: Subclinical demyelination frequently occurs in the optic, trigeminal, and facial nerves in IgG4 NF155(+) CIDP, suggesting that both central and peripheral myelin structures of the cranial nerves are involved in this condition, whereas nerve hypertrophy only develops in myelinated peripheral nerve fibers.